Reversing the Cycle : A Case Report on Managing Alopecia Areata with Syphilinum (Homoeopathy for All, 2026)
The following case report is  alopecia areata in 24 years old  male who was treated successfully  with individualised homoeopathic  medicine within 6 months of  treatment. Syphilinum was  prescribed as a constitutional remedy  on the basis of totality of symptoms  and after the repertorisation.  Homoeopathic medicines have  wonderful results in such type of  cases, where the modern medicines  have very less effective treatment.
Keywords: alopecia; areata; successfully; individualised; homoeopathic